The Myth of Worksharing - Arie Kapteyn; Adriaan S. Kalwij; Asghar Zaidi (Institute for the Study of Labor (IZA), 2000)
Worksharing is considered by many as a promising public policy to reduce unemployment. In this paper we present a review of the most pertinent theoretical and empirical contributions to the literature on worksharing. In addition, we also provide new empirical evidence on this issue, by a cross country analysis exploiting aggregate data for 13 OECD countries. The conclusions of the literature survey are indecisive. Conclusions about the efficacy of worksharing as an employment enhancing policy tool depend heavily on the setting in which the analysis takes place. Our empirical analysis does not find any evidence for the proposition that worksharing would promote employment or reduce unemployment. In an appendix we present an overview of recent public policy experience of European Countries with respect to different forms of worksharing. Also here the evidence is mixed.
Keywords: E24; J2; J3; C33; 330; Employment; hours of work; panel data; Job sharing; Arbeitszeitflexibilisierung; Arbeitslosigkeit; Beschäftigungseffekt; Theorie; OECD-Staaten